Adat, Istiadat dan Budaya Melayu Kalimantan Dalam Perspektif Arsitektur - Zain, Zairin; Akbar, Muhammad Alif Khairil; Situmeang, Meidycharlos Amos Ondion (RUAS, 2021)
Malays are one of several local ethnicities who inhabit the island of Kalimantan. Malay architecture can be linked to elements of customs, culture, and tradition that develop within the growth of ethnicity toward community development. Furthermore, many reports found that the characteristics of the environment and the settlements' location make a difference in the Malay house's traditional architecture on the island of Kalimantan. The study identifies some differentiation by the effects of cultural factors in each area of traditional architecture, affecting the architectural elements. The influences to Malay architecture are found differences by each region's customs, culture, and tradition. The Malays' customs, culture, and tradition greatly influence Malays houses' architecture because the culture is robust. This influence has made the customs, culture, and tradition become an obligation embedded in every Malay society. The embedded influences to the traditional Malay houses are found in the orientation of the openings, spatial arrangement, structure, and construction. The factor of being a Malay makes people attaching a unique meaning to the architecture of a traditional Malay house. The meanings follow the belief in environmental conditions and simplicity in Islamic teachings in traditional houses.